-4-3m=19

Simple and best practice solution for -4-3m=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-3m=19 equation:


Simplifying
-4 + -3m = 19

Solving
-4 + -3m = 19

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -3m = 19 + 4

Combine like terms: -4 + 4 = 0
0 + -3m = 19 + 4
-3m = 19 + 4

Combine like terms: 19 + 4 = 23
-3m = 23

Divide each side by '-3'.
m = -7.666666667

Simplifying
m = -7.666666667

See similar equations:

| (z-7)(z-7)= | | 5x-8=11+7x-2x | | (z-7)(z-7)=0 | | 2-27n=0 | | X+(x+2)+(x+4)=-15 | | 5x-8=11+7x-2 | | 0.75x+25=250.00 | | (X+1)(8x)=a | | 2(3x-3)=3(2x+2) | | 5y=-1x-3 | | r=2t+3 | | 8x=16+27 | | 2*(3x-8)+14=16 | | x*20/100=158 | | 2(3x-8)+14=16 | | x/6--1/x=1/3 | | x-20.7=9.5forx | | -8v=-9v+2 | | 7x-11=2(1-x) | | 3n+2n-4n= | | 20x-y=60 | | -4f+6=-6f | | 2m=3m+7 | | -4+3z=z | | 10+k=-k | | 4r=-3+3r | | 7+8w=9w | | 7w=6w+7 | | 2u=-2+u | | (6h+2)+(7h-8)= | | 2x(x+1)=8 | | 3(z-3)=3(z-4) |

Equations solver categories